(untitled) (International Journal of Innovative Computing, 2025)
The integration of multi-omics approaches has revolutionized cancer research by providing a comprehensive understanding of cancer pathogenesis beyond single-omics methods. By combining diverse omics data types, multi-omics analyses improve precision in identifying intricate disease-related mechanisms. Despite increasing interest, bibliometric analyses on multi-omics research in oncology remain limited. This study addresses this gap by conducting a bibliometric analysis of multi-omics cancer research trends over the past six years (2019 to February 2025), utilizing data from the Web of Science Core Collection (WoSCC) accessed on 28 February 2025, and analysing it with VOSviewer. The analysis of 3386 publications indexed in WoSCC reveals a significant surge in multi-omics research. China leads with 2055 publications, while the University of Toronto in Canada and the Institut National de la Santé et de la Recherche Médicale (Inserm) in France emerge as major contributors, each accounting for more than 50% of their country’s total publications in this domain. Dominant keywords such as multi-omics, prognosis, immunotherapy, machine learning and tumor microenvironment highlight current research priorities. This study provides a comprehensive overview of publication trends, offering valuable insights to guide future research in multi-omics cancer studies. By highlighting major contributors and emerging focal points, this study aspires to foster advancements and inspire future exploration in this pivotal domain.